Anaerobic treatment of olive mill wastewater and piggery effluents fermented with Candida tropicalis - Martinez-Garcia, Gregorio; Johnson, Anbu Clemensis; Bachmann, Robert T.; Williams, Ceri J.; Burgoyne, Andrea; Edyvean, Robert G.J. (Elsevier B.V., 2009)
Link to publisher's homepage at http://www.elsevier.com